Nuove forme di comunicazione sociale. L’emergere della communication voice - Gevisa La Rocca (Culture e Studi del Sociale)
The new forms of communication of good issues must be examined within the framework of change that mediatization produces on the expressive and organizational modalities of insti-tutions and individuals. It is necessary to consider the impact of media hype on the commu-nication of good issues, taking into account how the transmission of good issues has changed, in fact they - now - spread through social media, are supported by individual moti-vations and have a range of increasingly broader action. In this new guise the communication of good issues is called “antifragile” and its expressive modalities are defined as communica-tion voice.